2004
DOI: 10.1111/j.1365-2958.2004.04031.x
|View full text |Cite
|
Sign up to set email alerts
|

The Bacillus subtilisσW anti‐sigma factor RsiW is degraded by intramembrane proteolysis through YluC

Abstract: SummaryThe Bacillus subtilis s s s s W regulon is induced by different stresses such as alkaline shock, salt shock, phage infection and certain antibiotics that affect cell wall biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
194
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(202 citation statements)
references
References 48 publications
6
194
0
2
Order By: Relevance
“…Moreover, in B. subtilis, the MmpA homologue SpoIVFB cuts its substrate pro-s K apparently without assistance from a prior cleavage event (Rudner et al, 1999;Yu and Kroos, 2000). Finally, YluC, another MmpA homologue in B. subtilis, participates in the proteolysis of the anti-sigma factor RsiW, but neither of the two DegS homologues tested appears to play a role in RsiW degradation (Schobel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in B. subtilis, the MmpA homologue SpoIVFB cuts its substrate pro-s K apparently without assistance from a prior cleavage event (Rudner et al, 1999;Yu and Kroos, 2000). Finally, YluC, another MmpA homologue in B. subtilis, participates in the proteolysis of the anti-sigma factor RsiW, but neither of the two DegS homologues tested appears to play a role in RsiW degradation (Schobel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Members of this clan -including mammalian S2P, Escherichia coli YaeL, Enterococcus faecalis Eep, and B. subtilis SpoIVFB and YluC -cleave membrane-bound substrates (Fig. 1B) (Rawson et al ., 1997;An et al ., 1999;Rudner et al ., 1999;Zelenski et al ., 1999;Ye et al ., 2000;Yu and Kroos, 2000;Alba et al ., 2002;Kanehara et al ., 2002;Schobel et al ., 2004). Like their homologues, the predicted sequence of the Caulobacter proteins CC1916 and CC3381 contain HExxH and NPDG motifs that overlap or reside next to two of several transmembrane segments (Fig.…”
Section: Membrane Zinc Metalloprotease Mmpa Participates In Podj Procmentioning
confidence: 99%
See 1 more Smart Citation
“…A predominant paradigm is these ECF s positively control their own transcription and are located in operons together with their anti-regulators (Missiakas and Raina 1998;Raivio and Silhavy 2001;Bashyam and Hasnain 2004). These anti-s are often regulated by proteolysis and show increased degradation when stress increases and decreased degradation when stress decreases (Browning et al 2003;Schobel et al 2004;Reiling et al 2005). We suspect that the ability to immediately downregulate activity in response to decreased proteolysis will be an important design principle for the proteolytic cascades governing the activity of many Group 4 s and possibly in other systems governed by unstable negative regulators.…”
Section: Organization Of the Proteolytic Cascadementioning
confidence: 99%
“…We have suggested that RseP cleavage of full-length RseA is blocked so that DegS cleavage of RseA will be rate-limiting over a wide range of OMP signal. Interestingly, other RIP proteases that are widely used to transmit signals via a protease cascade between the compartments of a bacterial cell appear to occupy an intermediate position in every cascade: They transmit the signal rather than initiate the cascade and their activity is inhibited until the initial cleavage event is completed (Schobel et al 2004;Chen et al 2005;Matson and DiRita 2005). Cells use widely different proteins to accomplish inhibition; it remains an open question as to whether these inhibitory events are mechanistically similar or distinct (Resnekov and Losick 1998;Dong and Cutting 2003;Kroos 2004, 2005).…”
Section: Organization Of the Proteolytic Cascadementioning
confidence: 99%